Udan Rebon Paste Making Training for the People of Arar Village, Sorong Regency - Sukmawati, Sukmawati (Fakultas MIPA Universitas Negeri Padang, 2024)
Kampung Arar is a village that lives traditionally and has rich biodiversity, especially as rebon shrimp. The purpose of this training is to empower the people of Kampung Arar to take advantage of local potential, namely rebon shrimp into shrimp paste. The method of carrying out activities is by providing socialization on how to make rebon shrimp paste interactively, providing training on making rebon shrimp paste to the Arar village community, and monitoring training activities through observing participants' responses during the activity. In carrying out the activities, it was described about the expectations of the positive impact of this training on the people of Kampung Arar, including improving product quality, economic income. As a result of the training on making shrimp paste, the people of Kampung Arar were able to strengthen their local identity and open up new business opportunities. In addition, it is also hoped that there will be sustainable preservation of coastal ecosystems and the environment, so that the welfare and quality of life of the community can increase in a sustainable manner.